Metode Freeze Drying untuk Pengolahan Produk Kefir di Puri Farm Living, Kabupaten Tuban - Eka Lutfi Septiani; Qurrotin Arifianti; Anni Rahmat (Institut Pertanian Bogor, 2020)
Kefir is a food made from fermented milk of cows or goats which are believed to have many benefits including as a source of probiotics, maintaining bone health, and reducing cholesterol. Puri Farm Living is a kefir-producing business unit located in Tuban District which often faced the problem of declining of kefir liquid quality during the shipping process. Kefir liquid suffered damage caused by bacterial growth activities which can continuously press the container. Thus, the container is not able to accommodate it. In addition, kefir products have a fairly short expiration period if they are exposed in ambient temperature for more than 6 hours. Freeze drying is a method of drying food products at low temperatures to maintain the function of bacteria in kefir. The community service program aims to provide the partner member skills in operating the freeze drying device. The stages of the program includes: 1) problem survey and needs analysis, 2) design of freeze drying equipment, 3) testing and installation, 4) training, 5) monitoring and evaluation. The results indicate that partners are able to use the freeze drying device, both in the process of preparing raw materials, production, and packaging. In addition, the partner has succeeded to produce 150 capsules containing dried kefir that have not been damaged after more than 6 hours. Moreover, there are business units from other regions that highly want to apply this method in kefir processing. Therefore, this method has been considered quite effective to overcome the problem of distributing kefir products.